Tools of Empire? Vietnamese Catholics in South Vietnam - Nguyen-Marshall, Van (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2009)
This article examines the social and political activities of Vietnamese Roman Catholics in South Vietnam in the period from the 1950s to the 1970s. The Catholics’ participation in the public sphere, ranging from joining humanitarian organizations to organizing street protests, suggests that they were highly organized and proactive in trying to change their social and political environment. While Catholics held some political views and goals in common with the South Vietnamese and the United States governments, they pursued their own objectives, engaged in local and national politics, critiqued government policy, and maintained an important degree of independence from state power and influence.